Influence Of Orthodontic Treatment On Gingival Condition - Panainte, Irinel; Vlad, Ramona; Monea, Monica (European Scientific Journal, ESJ, 2016)
Aim of the study was to evaluate gingival modifications occuring in patients during orthodontic treatment with fixed appliances. Materials and methods. After inclusion and exclusion criteria were applied, in study were included 60 patients (35 girls and 25 boys). Mean age was 13.1 years for girls and 12.8 years for boys. Treatment period was 19.2 months for the upper arch and 21.3 months for the lower arch. There were taken 2 types of measurements ː plaque index (PI) and gingival index (GI), before, during and after treatment. Results. During orthodontic treatment buccal GI was 1.35 ± 0.32 and interpoximal GI was 1.75 ± 0.25. PI was 0.85 ± 0.28. After the appliances were removed, buccal GI was 1.44 ± 0.37, inteproximal GI 1.86 ± 0.22 and PI 1.01 ± 0.29. When PI and GI were measured in individual teeth it was found a statistical correlation in the measured values (p≤0.05). Conclusions. Based on these results we conclude that gingival modifications occur during orthodontic treatment. The most important changes are in the lower arch in molar area. After the treatment is finished, the situations come back in normal parameters.